Validation of metagenomic next-generation sequencing of bronchoalveolar lavage fluid for diagnosis of suspected pulmonary infections in patients with systemic autoimmune rheumatic diseases receiving immunosuppressant therapy - Wen, Sichun; Peng, Siqi; Hu, Xuejiao; Jiang, Nan; Li, Bohou; Chen, Boxi; Deng, Shuting; Yuan, Ye; Wu, Qiong; Tao, Yiming; Ma, Jianchao; Li, Sijia; et al. (Frontiers in Medicine, 2023)
Background: The accuracy and sensitivity of conventional microbiological tests (CMTs) are insufficient to identifiy opportunistic pathogens in patients with systemic autoimmune rheumatic diseases (SARDs). The study aimed to assess the usefulness of metagenomic next-generation sequencing (mNGS) vs. CMTs for the diagnosis of pulmonary infections in patients with SARDs receiving immunosuppressant therapy. Methods: The medical records of 40 patients with pulmonary infections and SARDs treated with immunosuppressants or corticosteroids were reviewed retrospectively. Bronchoalveolar lavage fluid (BALF)samples were collected from all patients and examined by mNGS and CMTs. Diagnostic values of the CMTs and mNGS were compared with the clinical composite diagnosis as the reference standard. Results: Of the 40 patients included for analysis, 37 (92.5%) were diagnosed with pulmonary infections and 3 (7.5%) with non-infectious diseases, of which two were considered primary diseases and one an asthma attack. In total, 15 pathogens (7 bacteria, 5 fungi, and 3 viruses) were detected by CMTs as compared to 58 (36 bacteria, 12 fungi, and 10 viruses) by mNGS. Diagnostic accuracy of mNGS was superior to that of the CMTs for the detection of co-infections with bacteria and fungi (95% vs. 53%, respectively, p < 0.01), and for the detection of single infections with fungi (97.5% vs. 55%, respectively, p < 0.01). Of the 31 patients diagnosed with co-infections, 4 (12.9%) were positive for two pathogens and 27 (87.1%) for three or more. The detection rate of co-infection was significantly higher for mNGS than CMTs (95% vs. 16%, respectively, p < 0.01). Conclusions: The accuracy of mNGS was superior to that of the CMTs for the diagnosis of pulmonary infections in patients with SARDs treated with immunosuppressants. The rapid diagnosis by mNGS can ensure timely adjustment of treatment regimens to improve diagnosis and outcomes.